Implementasi Konsep “Pinky Paw” pada Perancangan Interior Fasilitas Perawatan Anjing “ Pet Ground” di Surabaya - Olga Fellicia Setiawan; Ronald Hasudungan Irianto Sitindjak; Hendy Mulyono (Intra, 2019)
The main goal towards designing the interior of a dog care facility in Surabaya is to provide a place and service for dog owners as well as dog lover communities which resides in Surabaya. In addition, designing an interior for dog care facility also aims to educate dog owners as well as society in terms to care and treat dogs properly. The designed interior has various facilities to fulfill the needs of the owners as well as their pet dogs, these facilities include lobby for administration, a waiting room, a clinic, a swimming pool, a café, a grooming, training and playground facilities which all are designed with a fun concept.